Discordance between 10-year cardiovascular risk estimates using the ACC/AHA 2013 estimator and coronary artery calcium in individuals from 5 racial/ethnic groups: Comparing MASALA and MESA - Al Rifai, Mahmoud; Cainzos-Achirica, Miguel; Kanaya, Alka M.; Kandula, Namratha R.; Dardardi, Zeina; Joshi, Parag H.; Patel, Jaideep; Budoff, Matthew; Yeboah, Joseph; Guallar, Eliseo; Blumenthal, Roger S.; Blaha, Michael J. (Atherosclerosis, 2018)
South Asian (SA) individuals are thought to represent a group that is at high-risk for atherosclerotic cardiovascular disease (ASCVD). However, the performance of the Pooled Cohort Equations (PCE) remains uncertain in SAs living in the US. We aimed to study the interplay between predicted 10-year ASCVD risk and coronary artery calcium (CAC) in SAs compared to other racial/ethnic groups. We studied 536 SAs from the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study, and 2073 Non-Hispanic Whites (NHWs), 1514 African Americans (AAs), 1254 Hispanics, and 671 Chinese Americans (CAs) from the Multi-Ethnic Study of Atherosclerosis (MESA) who were not currently on statins. We used logistic regression models to assess the association between race/ethnicity and CAC within each ASCVD risk stratum. SAs at low and at intermediate estimated ASCVD risk were more likely to have CAC = 0 compared to NHWs, while SAs at high risk had a similar CAC burden to NHWs. For example, intermediate-risk SAs had a 73% higher odds of CAC = 0 compared to NHWs (95% 1.00–2.99), while high-risk SAs were equally likely to have CAC = 0 (OR 0.95, 95% CI 0.65–1.38) and CAC >100 (OR 0.86, 95% CI 0.61–1.22). Our results suggest that the extent of ASCVD risk overestimation using the PCEs may be even greater among SAs considered at low and intermediate risk than among NHWs. Studies with incident ASCVD events are required to validate and/or recalibrate current ASCVD risk prediction tools in this group. •The performance of the pooled cohort equations (PCE) among South Asians (SAs) is uncertain.•In the absence of 10-year follow-up for ASCVD events, coronary artery calcium may be used as a surrogate outcome.•We studied the prevalence of CAC across strata of ASCVD risk in SAs as well as in other 4 races/ethnicities.•There was a higher odds of CAC = 0 among low and intermediate risk SAs as compared to NHWs.•The PCE may overestimate risk in low and intermediate risk in SAs living in the US even to a greater extent than in NHWs.